The Liouville property for harmonic functions on groups and hypergroups - Heyer, H. (Methods of Functional Analysis and Topology, 2017)
A survey is given on the Liouville property of harmonic functions on groups and hypergroups. The discussion of a characterization of that property in terms of the underlying algebraic structures yields interesting open problems.